Ex Vivo MRI Evaluation of Breast Tumors: A Novel Tool for Verifying Resection of Nonpalpable Only MRI Detected Lesions. Issue 6 (19th September 2013) - Agresti, Roberto; Trecate, Giovanna; Ferraris, Cristina; Valeri, Barbara; Maugeri, Ilaria; Pellitteri, Cristina; Martelli, Gabriele; Migliavacca, Silvana; Carcangiu, Maria Luisa; Bohm, Silvia; Maffioli, Lorenzo; Vergnaghi, Daniele; et al.
Abstract A fundamental question in surgery of only magnetic resonance imaging (MRI)‐detected breast lesions is to ensure their removal when they are not palpable by clinical examination and surgical exploration. This is especially relevant in the case of small tumors, carcinoma in situ or lobular carcinoma. Thirty‐nine patients were enrolled in the study, 21 patients with breast lesions detected by both conventional imaging and breast MRI (bMRI) and 18 patients with bMRI findings only. Preoperative bMRI allowed staging the disease and localizing the lesion. In the operating theater, contrast medium was injected 1 minute before skin incision. After removal, surgical specimens were submitted to ex vivo MRI, performed using a dedicated surface coil and Spair inversion recovery sequences for suppression of fat signal intensity. All MRI enhancing lesions were completely included within the surgical specimen and visualized by ex vivo MRI. In the first 21 patients, bMRI was able to visualize branching margins or satellite nodules around the core lesion, and allowed for better staging of the surrounding in situ carcinoma; in the last 18 patients, eight of whom were breast cancer type 1 susceptibility protein (BRCA) mutation carriers, bMRI identified 12 malignant tumors, otherwise undetectable, that were all visualized by ex vivo MRI. This is the first description of a procedure that re‐enhances breast lesions within a surgical specimen, demonstrating the surgical removal of nonpalpable breast lesions diagnosed only with bMRI. This new strategy reproduces the morphology and the entire extension of the primary lesion on the specimen, with potentially better local surgical control, reducing additional unplanned surgery.